Improved health care utilization and costs in transplanted versus non-transplanted adults with sickle cell disease - Saraf, Santosh L.; Ghimire, Krishna; Patel, Pritesh; Sweiss, Karen; Gowhari, Michel; Molokie, Robert E.; Gordeuk, Victor R.; Rondelli, Damiano (PloS one, 2020)
Patients with sickle cell disease (SCD) have access to fewer health care resources and therapies compared to other diseases, which contributes to increased morbidity and health care utilization. We compared health care utilization (inpatient hospital days, emergency care visits) and health care-related costs between SCD adults that underwent hematopoietic stem cell transplantation (HSCT) using a nonmyeloblative conditioning regimen versus those referred for HSCT but did not proceed due to lack of an HLA-matched sibling donor, denial by insurance, red blood cell antibodies to the potential donor, or declining further evaluation. Between 8/2011 and 4/2016, 83 SCD patients were referred for allogeneic HSCT and 16 underwent the procedure. The HSCT and non-HSCT groups were similar by age, sex, prior SCD-related therapy and complications. Compared to pre HSCT, significantly fewer inpatient hospital days (median of 1 versus 22 days, P = 0.003) and emergency care visits (median of 1 versus 4 visits, P = 0.04) were observed by the 2nd year post-HSCT. Similar results were observed in comparison to the standard-of-care group (median of 1 versus 12 hospital days, P = 0.002; median of 1 versus 3 emergency visits, P = 0.03). Lower health care costs were observed by the 2nd year post-HSCT (median of $16,281 versus $64,634 pre-HSCT (P = 0.01) and versus $54,082 in the standard-of-care group (P = 0.05). A median reduction of -$20,833/patient/year (IQR, -$67,078-+$4,442/patient/year) in health care costs compared to pre-HSCT was observed in the 2nd year post-HSCT. In conclusion, allogeneic HSCT leads to improvements in health care utilization and costs compared to standard-of-care therapy in high-risk SCD adults.